Characterization of nanostructures ZnO synthesized through hydrothermal method - Mior Idris, Wan Nur Amalina (2015)
ZnO nanostructures can be derived using a variety of techniques. Using hydrothermal synthesis, ZnO nanostructures can be produced easily on a large scale due to the low temperature involved. Among the factors that influence the crystallinity of ZnO nanostructures are types of alkaline solution, the alkaline pH value used and the application hours of the hydrothermal process. This research focuses on the fabricated ZnO nanostructures via hydrothermal synthesis and the effects of alkaline solution on the morphology of ZnO nanostructures. Distilled water was mixed with three types of alkaline which are NaOH, KOH and LiOH solutions in 3 different pH values. The hydrothermal process was conducted using three different time periods which are 6, 12 and 24 hours. XRD analysis was done to identify the phase and crystallinity of ZnO nanostructures. Morphology and surface roughness analysis were characterized using FESEM and AFM to observe the nanostructures growing on ZnO thin films while current against voltage testing was done to identify the resistivity of ZnO nanostructures using a 2-probe point analyzer. All of these analyses were performed on the growth of ZnO nanostructures after the hydrothermal process. The results revealed that the addition of KOH solution as a precursor provides the best nanostructure properties over other alkaline solutions. The most suitable time period required to produce the best ZnO crystalline structure is 24 hours while the perfect pH value that allows the formation of ZnO nanostructures is 12.